GBA2-encoded β-glucosidase activity is involved in the inflammatory response to Pseudomonas aeruginosa. - Nicoletta Loberto (Public Library of Science (PLoS), 2014)
Current anti-inflammatory strategies for the treatment of pulmonary disease in cystic fibrosis (CF) are limited; thus, there is continued interest in identifying additional molecular targets for therapeutic intervention. Given the emerging role of sphingolipids (SLs) in various respiratory disorders, including CF, drugs that selectively target the enzymes associated with SL metabolism are under development. Miglustat, a well-characterized iminosugar-based inhibitor of β-glucosidase 2 (GBA2), has shown promise in CF treatment because it reduces the inflammatory response to infection by P. aeruginosa and restores F508del-CFTR chloride channel activity. This study aimed to probe the molecular basis for the anti-inflammatory activity of miglustat by examining specifically the role of GBA2 following the infection of CF bronchial epithelial cells by P. aeruginosa. We also report the anti-inflammatory activity of another potent inhibitor of GBA2 activity, namely N-(5-adamantane-1-yl-methoxy)pentyl)-deoxynojirimycin (Genz-529648). In CF bronchial cells, inhibition of GBA2 by miglustat or Genz-529648 significantly reduced the induction of IL-8 mRNA levels and protein release following infection by P. aeruginosa. Hence, the present data demonstrate that the anti-inflammatory effects of miglustat and Genz-529648 are likely exerted through inhibition of GBA2.